An evaluation of the introduction of the Global Navigation Satellite System for regional railways: Case studies from Italy. Issue 4 (30th December 2017) - Percoco, Marco; Siciliano, Giuseppe; Baccelli, Oliviero
Abstract: This paper aims to carry out a comprehensive cost-benefit analysis of the introduction of the Global Navigation Satellite System (GNSS) technologies into train control systems based on ERTMS (European standard) to increase the efficiency and safety of railway lines. To this end, the GNSS-based system is compared to other solutions along an appropriate time horizon. In our analysis, we consider several case studies from Italy and a range of benefit/cost ratios from 0.9 to 4.1 is found for the GNSS-based projects, depending on the different types of lines, their characteristics and their current endowment. Highlights: Cost-benefit analysis of the introduction of the Global Navigation Satellite System technology. Benefit/cost ratios range between 0.9 and 4.1.